Engaging the open science framework in quantifying and tracing scientists’ research credits - Chen, Zhiyi; Liu, Xuerong; Miao, Kuan; Liao, Xingya; Zhang, Xiaoling; Feng, Zhengzhi; Chuan-Peng, Hu (Frontiers in Integrative Neuroscience, 2023)
Graphical Abstract Preface illustration. The “first-last-author-credit” hierarchy has long been dominated in the scientific incentive system despite intensive calling for contribution-based credits (author contribution statement). In the scientific communities, senior researchers would still make a decision to recommend one’s promotion based on first and last positions in authorship rather than their contributions. Similarly, in the job market, institutions would acknowledge one’s credit by positions in authorship in a study for faculty recruitment, while overlooking the author contribution statement at the end of studies. Thus, the current authorship system has brought on the risks underlying authorship disputes and race/gender inequalities in credit allocation heavily, especially for early career researchers and female scientists. In addition, this is one of the major barriers to extend teamwork and academic collaboration. On the contrary, scrambling for first and last positions leads to prominent credit inflation—that is to be observed—the number of co-first and co-corresponding authors has been increasing dramatically. Thus, we shall propose a new contributionship to acknowledge the author’s credit for an open science and quantitative framework to tackle these issues. Credit: ZC and XRL.